Land use change and soil fertility assessment in the vicinity of Zagreb landfill. (2018) - Šestak, Ivana; Mesi?, Milan; Zgorelec, Željka; Per?in, Aleksandra; Bilandžija, Darija
The aim of this study was to give quantification of the present land use, land use change and assessment of agricultural soil in the area surrounding Jakuševec landfill in Zagreb, Croatia. A map of land use types of approximately 2 km zone around the landfill was created, based on photointerpretation during 2012 and according to Corine Land Cover 2000, 2006 and 2012 database. For soil fertility evaluation, soil was sampled at four locations at a distance of up to 300 m around the landfill. Spatial analysis revealed thirteen land use categories of total size around 3, 161 ha. These categories were divided into three larger groups based on land use types (water: 5%, agricultural land: 50% and city: 45% of the total analysed area). Mixed agriculture is very important in this urban area regardless of the closeness of the waste landfill, because it relies on fertile soil and vicinity of large market of the capital city. The main land use changes included increase in industrial or commercial units and transport infrastructure, and decrease of agricultural land.